2019
DOI: 10.1158/1078-0432.ccr-18-2811
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Tumor Microenvironment Modulation by EphB4-ephrinB2 Inhibition and Radiation Combination

Abstract: Purpose: A driving factor in pancreatic ductal adenocarcinoma (PDAC) treatment resistance is the tumor microenvironment, which is highly immunosuppressive. One potent immunologic adjuvant is radiotherapy. Radiation, however, has also been shown to induce immunosuppressive factors, which can contribute to tumor progression and formation of fibrotic tumor stroma. To capitalize on the immunogenic effects of radiation and obtain a durable tumor response, radiation must be rationally combined with targeted therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 72 publications
(91 reference statements)
0
10
0
Order By: Relevance
“…Studies on the expression of EphB4 in numerous cancer types have shown overexpressed level in breast, colorectal, lung, and blood cancers correlating with poor prognosis 11 13 . It has been reported that high EphB4 expression enhanced the growth and migration of pancreatic, colorectal and papillary thyroid carcinoma, and such effect could be reversed by EphB4 knockdown, making EphB4 a promising target for cancer treatment 14 16 . Our previous study has confirmed the high expression of EphB4 in HCC 17 , and its function in HCC migration remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the expression of EphB4 in numerous cancer types have shown overexpressed level in breast, colorectal, lung, and blood cancers correlating with poor prognosis 11 13 . It has been reported that high EphB4 expression enhanced the growth and migration of pancreatic, colorectal and papillary thyroid carcinoma, and such effect could be reversed by EphB4 knockdown, making EphB4 a promising target for cancer treatment 14 16 . Our previous study has confirmed the high expression of EphB4 in HCC 17 , and its function in HCC migration remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from its potential to induce tumor cell death, radiotherapy is known to recondition the tumor microenvironment and to stimulate systemic anti-tumor immune responses – a phenomenon summarized as abscopal effects of radiotherapy [266268]. However, in the monotherapy setting, radiation is often not sufficient to break the immunosuppressive milieu of established tumors, and combinations with immunostimulating agents are required.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy observed could be due to different detection techniques used. The total EphB4 expression was also seen to be higher in pancreatic cancer; however, relatively lower expression in the normal pancreas [ 29 ]. Public data repositories such as GTEx ( (accessed on 2 June 2021)) and the Human Protein Atlas ( (accessed on 2 June 2021)) show lower expression of EphB4 in the pancreas but a relatively higher expression in pancreatic cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The discrepancy observed could be due to different detection techniques used. The total EphB4 expression was also seen to be higher in pancreatic cancer; however, relatively lower expression in the normal pancreas [29]. Public data repositories such as GTEx (https://www.…”
Section: Eph Receptor Tyrosine Kinases Hyperphosphorylated In Pdac Pdxsmentioning
confidence: 99%
See 1 more Smart Citation